Indian and Eurasian Plates Are Active! Recent and Past Evidence - Ramprasad, B. Kesava (The International Hydrographic Review, 2005)
The recent tsunami caused by an earthquake of magnitude 9.0 at a focal depth of 30km, which occurred on 26 December 2004 (00:58:50 UTC) with the epicentre at 3.298°N, 95.779°E, cost thousands of lives and extensive property damage in south-eastern Asian and East African countries viz., Indonesia, Sri Lanka, India, Thailand, Somalia, Myanmar, Maldives, Malaysia, Tanzania, Seychelles, Bangladesh, Kenya and South Africa (source: USGS). As of 5 January 2005, the confirmed deaths were 1,58,240 in all the aforesaid tsunami affected countries (Blogger™ News Agency, source: Wikipedia, 10:20pm ET, 05 Jan’05). Out of which 94,081 died in Indonesia alone and 48,677 in Sri Lanka. In India nearly 10,000 people lost their lives mostly in the Andaman and Nicobar Islands and the coastal districts of Tamilnadu, Kerala and Andhrapradesh. The epicentre of the earthquake was identified as being located off the coast of Sumatra, Indonesia in the Indian Ocean. Apart from the tsunami generated casualties it is also likely that direct earthquake induced damages also affected the Andaman and Nicobar group of islands. The earthquake took place in a most active seismic region characterised by tectonic features of the north-south trending Indo-Burma ranges in the north, Andaman-Nicobar islands and the Sumatra fault system in the southeast. According to the available fault plane solutions (USGS) the event took place due to thrust type movement.